The Effect of the Relationship of APOE Polymorphisms and Cerebral Vasospasm on Functional Outcomes in Children With Traumatic Brain Injury. Issue 5 (October 2018) - Reuter-Rice, Karin; Regier, Michael; Bennett, Ellen; Laskowitz, Daniel
Background: Pediatric traumatic brain injury (TBI) is a leading cause of death and disability. Polymorphisms in the apolipoprotein E ( APOE ) gene have been linked to cerebral vasospasm (CV) and poor outcomes in adults with TBI, yet these associations remain poorly defined in children. Objective: We examined the effect of the relationship between APOE polymorphisms and CV on functional outcomes in children with a TBI. Method: This prospective, descriptive study examined 60 children (aged 10 days to 15 years) with a TBI. Data included demographic information, genetic sampling for the APOE gene and single-nucleotide polymorphisms (SNPs; rs405509, rs429358, rs7412), and daily transcranial Doppler ultrasounds to evaluate for CV. We examined Glasgow Outcome Scale–Extended Pediatrics (GOS-E Peds) scores at the time of discharge and 4–6 weeks after discharge. Results: More than half (56.7%) of the 60 children ( M age = 5.9 years) were male. Twenty-six participants (43.3%) experienced an occurrence of CV. There were significant differences in injury mechanism (unadjusted p = .048) and age (unadjusted p = .02) between those with and without CV. Also, the noncoding promoter SNP rs405509 T/T, when considered with injury severity, appeared to modify the relationship of APOE genotype to CV. The relationship between APOE and CV had no significant effect on GOS-E Peds scores. Conclusion: Injury severity and the APOE noncoding promoter SNP rs405509 may modify the relationship between APOE and CV in children with TBI. More studies are needed to understand the role of APOE polymorphisms in outcomes in children with TBI.